The Trojan horse - neuroinflammatory impact of T cells in neurodegenerative diseases - Sommer, Annika; Winner, Beate; Prots, Iryna (Molecular Neurodegeneration, 2017)
Neuronal degeneration is a common mechanism of many neurological diseases including Parkinson's disease (PD), Alzheimer's disease (AD), and Multiple Sclerosis (MS). While AD and PD are classical neurodegenerative diseases, the primary pathology in MS is driven by autoimmune inflammation, attacking oligodendrocytes and thereby inducing neurodegeneration. In AD and PD, immune cells are also considered to play an important role in the disease progression. While the role of local central nervous system (CNS) innate immune cells is well described, a potential influence of adaptive immune cells in PD and AD is not yet fully understood.Here, we aim to summarize findings concerning adaptive immune cells in PD pathogenesis and compare them to AD and MS. In the first part, we focus on disease-specific alterations of lymphocytes in the circulating blood. Subsequently, we describe what is known about CNS-infiltrated lymphocytes and mechanisms of their infiltration. Finally, we summarize published data and try to understand the mechanisms of how lymphocytes contribute to neurodegeneration in PD, AD, and MS.Lymphocytes are critically involved in the pathogenesis of MS, and clarifying the role of lymphocytes in PD and AD pathogenesis might lead to an identification of a common signature of lymphocytes in neurodegeneration and thus pave the road towards novel treatment options.
EVALuna2:34020